Evolutionary Programming (EP) based technique for secure point identification with load shedding technique in power transmission / Abdul Rahman Minhat - Minhat, Abdul Rahman (2008)
Voltage stability has been identified as a crucial issue in power system study which has been identified as one of the causes that lead to cascading power system blackout in many parts of the world. This phenomenon has made this subject a very relevant issue in power system planning and operation. This thesis presents the Evolutionary Programming (EP) based technique for secure point identification with load shedding technique in power transmission system. The study was initiated by the development of new algorithm for automatic voltage stability assessment (AVSA). This algorithm is used to estimate the maximum loadability point in power system. Consequently, another algorithm for maximum loadability identification using EP optimization technique was also developed. Several load buses have undergone maximum loadability tests for the determination of secure point prior to system instability occurrence, which may lead to possibility of voltage collapse in the system. In highlighting the merit of the proposed EP based technique for maximum loadability identification, established artificial immune system (AIS) optimization technique and AVSA were utilized for comparative studies purposes. The strength of EP in this study was evaluated in terms of its capability to search for the accurate solution and fast computation time. Consequently, the algorithm for load increase simultaneously at several load buses was also developed in order to search the optimal value at each bus in a system such that the system can maintain a stable condition. The ability of EP to search for the optimal values of multi-load increase as compared to AVSA which is only able to conduct uniform load increase at several load buses has been identified as the strength of EP over AVSA.